1984
DOI: 10.1002/hep.1840040521
|View full text |Cite
|
Sign up to set email alerts
|

Centrilobular Liver Necrosis Induced by Hypoxia in Chronic Ethanol-Fed Rats

Abstract: Rats fed ethanol from 21 to 130 days were subjected to one or more episodes of hypoxia (6% O2) in order to determine if ethanol predisposed to centrilobular liver necrosis induced by hypoxia. Pair-fed control rats were fed the diet regimen in parallel with the ethanol-fed rats through an indwelling gastric cannula. The diet and ethanol were fed continuously 24 hr per day so as to maintain high blood alcohol levels in the ethanol-fed rats. Serum enzyme levels, SGOT and SGPT were measured before and after the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(43 citation statements)
references
References 22 publications
2
40
0
1
Order By: Relevance
“…Our findings also help to explain why hypoxia may occur in the liver with alcohol feeding (49,50). Increased mitochondrial respiration and increases in the number of mitochondria consuming oxygen for alcohol metabolism may underlie hypoxia in the liver with alcohol feeding.…”
Section: Nadmentioning
confidence: 69%
“…Our findings also help to explain why hypoxia may occur in the liver with alcohol feeding (49,50). Increased mitochondrial respiration and increases in the number of mitochondria consuming oxygen for alcohol metabolism may underlie hypoxia in the liver with alcohol feeding.…”
Section: Nadmentioning
confidence: 69%
“…In the TsukamotoFrench model, the rate of ethanol elimination, which is oxygen dependent, was elevated 2-to 3-fold in rats exposed to ethanol for 2 to 4 weeks; however, when Kupffer cells were destroyed by GdCl 3 , this phenomenon was blocked. Indeed, centrilobular pathological changes are compatible with a mechanism involving hypoxia, and injury was increased when O 2 tension in the liver was decreased (17). Importantly, conditioned media from isolated Kupffer cells from ethanol-treated rats stimulated parenchymal cell oxygen consumption.…”
Section: Gender Studiesmentioning
confidence: 95%
“…In the liver, infusion ofethanol into the portal vein elicits vasoconstriction in the hepatic microvasculature, leading to hepatic tissue hypoxia and eventually hepatocellular necrosis (5,6). French et al reported that ethanol-induced perturbation of microcirculation plays an important role in the pathogenesis of alcoholic liver damage (7)(8)(9)(10). Accordingly, a method to inhibit this vasoconstrictive effect of ethanol would be expected to effectively reduce the incidence Preliminary reports of portions ofthis work were presented at the 42nd Annual Meeting of the American Association for the Study of Liver Disease, Chicago, IL, 2-5 November 1991. and morbidity of alcoholic liver damage.…”
Section: Introductionmentioning
confidence: 99%